1) 7 - 2x ≤ 10 - 3х;
Перенесем свободный член вправо:
3х - 2x ≤ 10 - 7;
x1 ≤ 3;
х1 ∈ (- ∞; 3];
2) 3x + 12 > 4х - 1;
3x - 4х > - 12 - 1;
- x > - 13;
Разделим на ( - 1), изменив знак неравенства:
x < - 13 / ( - 1);
x2 < 13;
х2 ∈ (- ∞; 13);
Нанесем общие значения на координатную ось:
---•(3)--- °(13)---
х ∈ (- ∞; 3];
ответ: х ∈ (- ∞; 3].
1) 7 - 2x ≤ 10 - 3х;
Перенесем свободный член вправо:
3х - 2x ≤ 10 - 7;
x1 ≤ 3;
х1 ∈ (- ∞; 3];
2) 3x + 12 > 4х - 1;
Перенесем свободный член вправо:
3x - 4х > - 12 - 1;
- x > - 13;
Разделим на ( - 1), изменив знак неравенства:
x < - 13 / ( - 1);
x2 < 13;
х2 ∈ (- ∞; 13);
Нанесем общие значения на координатную ось:
---•(3)--- °(13)---
х ∈ (- ∞; 3];
ответ: х ∈ (- ∞; 3].